The Use of Podcast in Improving Listening Skill of EFL Students at SMA Negeri 12 Makassar - Ririn Febrianti; Ahmad Talib; Amra Ariyani (State University of Makassar, 2023)
This study was a pre-experimental research that aimed to find out whether the use of podcast improves EFL students' listening skill at SMAN 12 Makassar. The independent variable of this study is the use of podcast and the dependent variable is the students' listening skill. The population of this study was all of the students of XI MIPA Classes of SMAN 12 Makassar and the sample was XI MIPA 2 class with 36 students. The research sample was selected by using a cluster random sampling. The research data were obtained by giving a multiple choices listening tests in the pretest and posttest. The analysis technique used in this research was descriptive statistical and inferential statistical techniques. Based on the analysis results, P = 0.000 is smaller than Î± = 0.05 and the studentsâ€™ mean score in posttest (77.77) was higher than the studentsâ€™ mean score in the pretest (56.25). So, it was concluded that the use of podcast significantly improved the listening skill of EFL students at SMAN 12 Makassar. This research only focused on the use of audio podcast on Spotify in improving students' listening skill. Future researchers may be able to conduct research to find out how audio podcasts or other types of podcasts can improve other skills such as speaking, reading, and writing.Key words– podcast, listening skill